1992
DOI: 10.1007/bf02783995
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the platelet thromboxane A2 and aortic prostacyclin synthesis by dietary selenium and vitamin E

Abstract: Vitamin E and selenium (Se) interact synergistically as an important antioxidant defense mechanisms. Se, an essential component of glutathione peroxidase (GSH-Px) and vitamin E decompose fatty acid hydroperoxides and hydrogen peroxides generated by free radical reactions. Vitamin E and GSH-Px may modulate arachidonic acid metabolism and the activity of cyclooxygenase enzymes by affecting peroxide concentration. The balance between arterial wall prostacyclin (PGI2) production and platelet thromboxane (TX)A2 dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…30 In the present study, interestingly, liver and heart arginase activities in the combination group recovered to the level of control group after 48 h of prednisolone administration (Tables 2 and 4). This observation may suggest that vitamin E and Se in combination may prevent changes in arginase activity caused by prednisolone in different tissues.…”
Section: Discussionsupporting
confidence: 60%
“…30 In the present study, interestingly, liver and heart arginase activities in the combination group recovered to the level of control group after 48 h of prednisolone administration (Tables 2 and 4). This observation may suggest that vitamin E and Se in combination may prevent changes in arginase activity caused by prednisolone in different tissues.…”
Section: Discussionsupporting
confidence: 60%
“…Sey and Schutz 25 reported that the metabolism of two essential fatty acids, linoleic and arachidonic acids are aected by vitamin E and Se. In addition, Meydani 9 indicated that both vitamin E and GSH±Px may modulate arachidonic acid metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Meydani 9 reported that vitamin E and Se have many synergistic functions in cells. One of the most important functions is antioxidant action, which operates both intracellularly and intercellularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant defense is achieved by additive or synergistic action of enzymes and antiox-idant nutrients (11,12). Selenium and vitamin E in particular appear to have overlapping and partly compensative functions (13)(14)(15)(16)(17). Therefore, it is conceivable that the relation between selenium status and risk of coronary heart disease is influenced by the status of other antioxidants, as has been observed in an animal experiment (18).…”
mentioning
confidence: 98%